DNA-binding and strand-annealing activities of human Mre11: implications for its roles in DNA double-strand break repair pathways - de Jager, Martijn (Oxford University Press, 2001)
DNA double-strand breaks (DSBs) in eukaryotic cells can be repaired by non-homologous end-joining or homologous recombination. The complex containing the Mre11, Rad50 and Nbs1 proteins has been implicated in both DSB repair pathways, even though they are mechanistically different. To get a better understanding of the properties of the human Mre11 (hMre11) protein, we investigated some of its biochemical activities. We found that hMre11 binds both double- and single-stranded (ss)DNA, with a preference for ssDNA. hMre11 does not require DNA ends for efficient binding. Interestingly, hMre11 mediates the annealing of complementary ssDNA molecules. In contrast to the annealing activity of the homologous recombination protein hRad52, the activity of hMre11 is abrogated by the ssDNA binding protein hRPA. We discuss the possible implications of the results for the role(s) of hMre11 in both DSB repair pathways.